The cut-off value for HOMA-IR discriminating the insulin resistance based on the SHBG level in women with polycystic ovary syndrome - Biernacka-Bartnik, Aleksandra; Kocełak, Piotr; Owczarek, Aleksander Jerzy; Choręza, Piotr Stanisław; Markuszewski, Leszek; Madej, Paweł; Puzianowska-Kuźnicka, Monika; Chudek, Jerzy; Olszanecka-Glinianowicz, Magdalena (Frontiers in Medicine, 2023)
Introduction: The study aimed to estimate the cut-off value for homeostatic model assessment for insulin resistance (HOMA-IR) discriminating the insulin resistance based on the sex hormones binding globulin (SHBG) level in women with polycystic ovary syndrome (PCOS). Material and Methods: Data from medical records of 854 Caucasian women diagnosed with PCOS were analyzed. Anthropometric data, fasting plasma glucose, insulin and SHBG levels were measured. HOMA-IR was calculated with a standard formula. The cut-off value was calculated using receiver-operating characteristics. Results: Circulating SHBG levels below the normal range (26.1 nmol/L) were found in 25.4% of study participants. This subgroup had a significantly higher BMI, fasting glucose and insulin concentrations and HOMA-IR values. Empirical optimal cut-off values for HOMA-IR corresponding to low SHBG levels was ≥ 2.1 (area under the curve [AUC] 0.73, accuracy 0.65, sensitivity 72.3%, specificity 63.1%, positive predictive value [PPV] 40.0%, negative predictive value [NPV] 87.0%). Conclusion: Our study suggests that the cut-off point for HOMA-IR discriminating the insulin resistance based on the SHBG level, in young Caucasian women with polycystic ovary syndrome is 2.1, and is consistent with the cut-off value adopted by the European Group for the Study of Insulin Resistance (above 2.0).